Managers’ environmental commitment towards the adoption of environmental strategies: Exporting Ecuadorian SMEs - Cervantes, Michelle Alexandra (European Public & Social Innovation Review, 2024)
Introduction: Over the past few decades, sustainability and natural environmental degradation have grown in importance around the world. However, studies on internationalization and corporate environmental responsibility have frequently concentrated on larger businesses in industrialized nations. Methodology: This study examines the owners' engagement and environmental attitude in Ecuadorian exporting SMEs using four case studies. Results: The results indicate that the firm's green commitment and the owners' environmental attitude and involvement may be influenced by their prior knowledge, environmental goals. Additionally, human and financial resources are crucial to the company's adoption of eco-friendly practices. Discussion: In exporting Ecuadorian companies, a conceptual framework was created that describes the connection between the owners' past knowledge, their attitude toward the environment, and the company's green commitment. Conclusions: the article expands the literature in dynamic capabilities, top management commitment and environmental responsibility.